Design of Uniform and Non Uniform Circular Arrays Comparison with FFA and RLS - Suraya Mubeen, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Multiple antennas can be arranged in various geometrical configurations to form an antenna array with high directive radiation pattern. Linear antennas are limited in their steering capability. The circular arrays have become popular in recent years over other array geometries because they have the capability to perform the scan in all the directions without a considerable change in the beam pattern and provide 3600 azimuth coverage. Circular arrays which are used for design is compared to linear and rectangular arrays as they does not have edge elements. They can be used for beam forming in the azimuth plane for example at the base stations of the mobile radio communication systems as the components for signal processing. FFA design method of circular apertures for narrow beam width and low side lobes has been reported by Taylor. It includes the development of continuous circular aperture distributions, which contain only two independent parameters A and , where A is related to the design of side lobe level,Â is a number controlling the degree of uniformity of the side lobes. A radiation pattern is expressed in the integral form. They are compared with a line source and circular aperture.Â Â